GROUNDING OF MONITORING THE STABILITY OF PILLARS AND ROOF AT MINES BY MEANS OF INFORMATION CRITERION - Voznesenskij A.S.; Zakharchenko G.V. (My University, 2001)
Ways for improving the truth of seismic monitoring of roof state, rock thickness and pillar state have been considered. It has been shown that probability of correct identification of rock mass state can be improved by means of increasing the quantity of information parameters and calculating their derivatives. Calculations of minimal quantity of information parameters have been performed on basis of large-scale observations and information criteria. Bayes criterion is used for decision making about rock mass state. Methods of multiparameter recognition of images are applied in this case. Continuous measurement of seismic conditions is provided.